4 - Ethnomathematics, Geometry and Educational Experiences in Africa: DOI: 10.4314/ad.v30i3.22229 - Gerdes, Paul (Africa Development, 2005)
The paper traces historically reflections about mathematics, education and culture in Africa, that culminated in the emergence of ethnomathematics as a research field. A brief overview of ethnomathematical research in Mozambique and ofhistorical research related to mathematics in Africa is presented, followed by examples of the integration of ethnomathematics into teacher education to stimulate the development of social—and cultural—mathematical awareness. The paper concludes with some trends in using ideas from ethnomathematics in education in Africa.